(untitled) (Journal of Life and Earth Science, 2011)
Attempts were made to examine the interactive relations of gender, residence and social stratification with different types of aggressive behaviour. The independent variables were gender, residence and socio-economic status. Different types of the behaviour include physical, verbal, anger, hostile and indirect aggression. A total of 240 respondents between 13 and 16 years of age constituted the sample of the study. The Measure of Aggressive Behaviour (MAB) was used for data collection. The study utilized a 2 × 2 × 3 factorial design consisting of two levels of gender (male/female), two levels of residential background (urban/rural), and three levels of socio-economic status (high/middle/low). The results were computed on each dimension separately using t-tests. The findings revealed interactive relations of gender, residence and social stratification with different types of aggression. Key words: Aggression; antisocial behaviour; gang related violence; autism; attention deficit disorder DOI: 10.3329/jles.v2i2.7500 J. Life Earth Sci., Vol. 2(2) 67-74, 2007